2019
DOI: 10.18178/ijcea.2019.10.4.748
|View full text |Cite
|
Sign up to set email alerts
|

Anti-amoeba Effect of Branched Medium Chain Fatty Acids and Their Salts on Acanthamoeba Castellanii

Abstract: Acanthamoeba castellanii is an organism that causes Acanthamoeba keratitis, an infectious disease. Acanthamoeba are protists that generally inhabiting soils, freshwater, and sea water, but can also infect the cornea due to dirty water infiltration if contaminated contact lenses are worn. In this study, we focused on four branched medium chain fatty acids-2-ethylhexanoic acid, 3,5,5-trimethylhexanoic acid along with their salts, potassium 2-ethylhexanoate, and potassium 3,5,5-trimethylhexanoate. We examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…150 mM (5.0 w/ v%) of iso-C18K reduced the growth of A. castellanii by 4 log units after 10 minutes of incubation, whereas control (pH-adjusted water) was ineffective. Sasaki et al (2019) examined the anti-amoeba effect using samples of 3,5,5-trimethylhexanoic acid (2800 mM) and potassium 3,5,5-trimethylhexanoate (260 mM) . As a result, it was confirmed that 3,5,5-trimethylhexanoic acid decreased by 4 orders in 10 minutes and potassium 3,5,5-trimethylhexanoate decreased by 4 orders in 180 minutes.…”
mentioning
confidence: 99%
“…150 mM (5.0 w/ v%) of iso-C18K reduced the growth of A. castellanii by 4 log units after 10 minutes of incubation, whereas control (pH-adjusted water) was ineffective. Sasaki et al (2019) examined the anti-amoeba effect using samples of 3,5,5-trimethylhexanoic acid (2800 mM) and potassium 3,5,5-trimethylhexanoate (260 mM) . As a result, it was confirmed that 3,5,5-trimethylhexanoic acid decreased by 4 orders in 10 minutes and potassium 3,5,5-trimethylhexanoate decreased by 4 orders in 180 minutes.…”
mentioning
confidence: 99%